Spillover Through Shared Agendas: Understanding How Social Movements Set Agendas for One Another - Ring-Ramirez, Misty; Earl, Jennifer (PARTECIPAZIONE E CONFLITTO, 2021)
Social movement spillover is an internal social movement sector outcome in which movements influence one another. Although research on social movement outcomes has advanced significantly in recent years, there has been less work on consequences that movements have on one another. One reason for this is that research on social movement spillover has been limited by its reliance on a small number of research methods, nearly all of which involve pre-selecting movements that are expected to be at risk of spillover. In this article, we contribute important new findings to the study of spillover in two ways. First, we examine a novel form of spillover: agenda spillover, which occurs when the goals of one movement come to be taken up by another movement in a serious or enduring manner (e.g., when racial justice goals become embedded in environmental goals). Second, using social network and computational methods, validated by significant pre-study testing, and event history analysis, we examine what factors seem to explain agenda spillover. We find that the social movement sector, characteristics of social movements themselves and, to a lesser extent, the political context, affect the propensity for movements to experience agenda spillover.